Spline‐Based Drift Analysis for the Reliability of Semiconductor Devices. Issue 8 (10th July 2021) - Hofer, Vera; Nowak, Thomas; Lewitschnig, Horst
Abstract: Design and production of semiconductor devices for the automotive industry are characterized by high reliability requirements, such that the proper functioning of such devices is ensured over their whole lifetime. Manufacturers subject their products to extensive testing, such as high‐temperature operating life (HTOL) tests that simulate the tough requirements products have to withstand. In the present study, the drift behavior of a representative electrical parameter under HTOL stress conditions is modeled, using linear splines, and a model for the determination of test limits used to ensure reliability is formulated. These test limits are computed such that for a predefined probability the electrical parameters under consideration remain within their specification limits over the whole product lifetime. Additionally, the yield loss that might be caused by this quality control procedure should be kept as small as possible. These test limits can then be used by automated test equipment to detect conforming and non‐conforming devices immediately after production. Extensive numerical simulations are conducted in order to demonstrate the performance of this model under a wide set of different scenarios for inter‐ and intra‐device variabilities. Abstract : A model is presented for setting yield‐loss minimizing test limits in order to separate conforming and non‐conforming electronic devices using automated test equipment in high‐temperature operating life (HTOL) tests. These test limits are computed based on a spline model which reflects the drift behavior of an electrical parameter under HTOL stress conditions.